Recent Advances in Glutathione Depletion-Enhanced Porphyrin-Based nMOFs for Photodynamic Therapy - Bin Gong; Qiuyun Zhang; Jiayi Chen; Yijie Qu; Xuanxuan Luo; Weiqi Wang; Xiaohua Zheng (Pharmaceutics)
Photodynamic therapy has established itself as a clinical treatment for certain superficial cancers by converting oxygen into cytotoxic singlet oxygen to eradicate cancer cells. Porphyrin-based nanoscale metal–organic frameworks have emerged as promising photosensitive platforms due to their ability to prevent the hydrophobic aggregation quenching of porphyrin molecules and enhance accumulation at the tumor site, thereby becoming a focal point in photodynamic materials research. However, the elevated levels of glutathione and other reductive substances within cancer cells can alleviate the oxidative stress induced by singlet oxygen from the photodynamic therapy process, thus protecting intracellular biomolecular structures from damage. Consequently, it is crucial to design functionalized nanoplatforms that integrate glutathione depletion with porphyrin-based metal–organic frameworks to significantly boost photodynamic therapy efficacy. Moreover, the excess glutathione within cells can disrupt the structure of porphyrin-based metal–organic frameworks, which not only increases the capacity of porphyrin molecules to generate singlet oxygen upon light exposure but also aids in the recovery of their fluorescence imaging capabilities. Additionally, this specificity minimizes the photosensitizing harm of porphyrin-based metal–organic frameworks to other normal tissues. This review compiles recent advancements in developing porphyrin-based metal–organic frameworks for enhanced phototherapy through glutathione depletion. It aims to promote the further application of porphyrin-based metal–organic frameworks in phototherapy and provide valuable insights for preclinical applications. By highlighting strategies that improve therapeutic outcomes while maintaining safety profiles, this summary seeks to advance the development of more effective and targeted cancer treatments.